DAMPAK PERJANJIAN PERDAGANGAN BARANG ASEAN-KOREA SELATAN FREE TRADE AREA (AKFTA) TERHADAP INDONESIA TAHUN 2007-2011 - Era Rahmawati; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research is about trade relations between Indonesia and South Korea within the framework of AKFTA. Like other economic cooperation that attempts to realize free trade, cooperation, AKFTA cooperation aims to facilitate the flow of goods and capital. This cooperation runs international trade principles promoted by the global trade regime of the World Trade Organization (WTO).The purpose of the research is to see how the impact of the trade agreement AKFTA of Indonesia.This study used a qualitative research method. In this research, the author uses liberalist prespective with international cooperate theory with level analysis in nation-state. And data collection tecnique through the study of literature (Library Research).The result showed that the cooperation of the Free Trade Area (FTA) within the scope of ASEAN-South Korea Free Trade Area (AKFTA) involving Indonesia had a positive impact on the Indonesian economy, because in this case can be seen from the increase in the value of Indonesia's exports to South Korea from year to years (2007-2011), then the increase of investment of the investors from South Korea who invest capital in Indonesia, and also have a positive impact on the development of Indonesia, because South Korea has provided monetary assistance for the development of Indonesia.Keywords: ASEAN-South Korea Free Trade Area (AKFTA), Free Trade Area (FTA), Economy